(untitled) (Journal of the Bangladesh Agricultural University, 2019)
Efficacy of turmeric (Curcuma longa) and neem (Azadirachta indica) or repelling dry fish insects (Dermestes sp. adult and larva) was investigated on the basis of their repellency rate, storage quality, sensory attributes of turmeric and neem treated dry fish and their cooked products. Pesticides prepared from turmeric and neem, were used in the form of extract and powder. The extracts were tested at the concentrations of 2%, 3%, 5% for turmeric and 3%, 5%, 7% for neem. Turmeric and neem powder were used for treatment at the rate of 2.0%, 3%, 4.0% upon 100 g dry fish. Repellency rate of Dermestes sp., adults was highest, where larvae showed mere resistance against herbal pesticides. Pesticides prepared from turmeric were more repellent than neem pesticides. Control and treated dry fish had almost similar sensory attributes after the 2nd month. However, odor, texture, general appearance and insect occurrence of control dry fish decreased significantly after 4th month of storage but all those parameter of treated dry fish were nearly unchanged. However, sensory quality of dry fish treated with turmeric and neem were remain unchanged after the 4thmonth. The results suggested that 3% extract and powder of turmeric or neem at the rate of 5% extract and 3% powder can be used as suitable field doses for direct application in dry fish to prevent insect infestation during storage of dry fish products. J. Bangladesh Agril. Univ. 17(1): 110–116, March 2019